Admission serum albumin concentrations and response to nutritional therapy in hospitalised patients at malnutrition risk: Secondary analysis of a randomised clinical trial. (March 2022) - Bretscher, Céline; Boesiger, Fabienne; Kaegi-Braun, Nina; Hersberger, Lara; Lobo, Dileep N.; Evans, David C.; Tribolet, Pascal; Gomes, Filomena; Hoess, Claus; Pavlicek, Vojtech; Bilz, Stefan; Sigrist, Sarah; et al.
Summary: Background: Historically, admission serum albumin concentrations have been considered useful biochemical markers for nutrition assessment. However, there is a lack of randomised trial data investigating whether low albumin concentrations are helpful for identifying patients benefitting from nutritional support. Methods: This study was a secondary analysis of the EFFORT trial, a Swiss-wide multicentre, randomised controlled trial comparing individualised nutritional support with usual care nutrition in medical inpatients from April 1, 2014, to February 1, 2018. 1389 of 2028 patients at nutritional risk with available albumin concentrations on admission were included. The primary endpoint was all-cause mortality within 30 and 180 days. Patients were stratified into groups of low or normal albumin based on the albumin cut-off of 30 g/L. ClinicalTrials.gov number, NCT02517476. Findings: 1389 patients (mean age, 73.1 (SD 3.5) years; 747 (53.8%) men) were included and 676 (48.7%) had low serum albumin concentrations at admission (<30 g/L). Mortality at 180 days was significantly increased in the low albumin group compared with patients with normal albumin concentrations (219/676 (32.4%) vs. 162/713 (22.7%), fully adjusted HR 1.4, 95%CI 1.11 to 1.77, p = 0.005]. Effects of nutritional support on 30-day mortality were similar for patients with low compared to patients with normal albumin concentrations (HR 0.68, 95%CI 0.44 to 1.05 vs. HR 0.70, 95%CI 0.41 to 1.20), with no evidence for a subgroup effect ( p for interaction=0.97). Interpretation: Based on this secondary analysis of a randomised trial, low admission serum albumin concentrations in hospitalised, non-critically ill, medical patients at nutritional risk had prognostic implications and indicated higher mortality risk but were not helpful in selecting patients for nutritional interventions. Funding: The Swiss National Science Foundation (SNSF) (PP00P3_150531) and the Research Council of the Kantonsspital Aarau (1410.000.058 and 1410.000.044) provided funding for the EFFORT trial